A New Herbal Formula, KSG-002, Suppresses Breast Cancer Growth and Metastasis by Targeting NF-κB-Dependent TNFα Production in Macrophages - Woo, Sang-Mi (Hindawi Publishing Corporation, 2013)
Tumor-associated macrophages (TAMs) in tumor microenvironment regulate cancer progression and metastases. In breast cancer, macrophage infiltration is correlated with a poor prognosis. While metastatic breast cancer is poor prognostic with a severe mortality, therapeutic options are still limited. In this study, we demonstrate that KSG-002, a new herbal composition of radices Astragalus membranaceus and Angelica gigas, suppresses breast cancer via inhibiting TAM recruitment. KSG-002, an extract of radices Astragalus membranaceus and Angelica gigas at 3 : 1 ratio, respectively, inhibited MDA-MB-231 xenograft tumor growth and pulmonary metastasis in nude mice, while KSG-001, another composition (1 : 1 ratio, w/w), enhanced tumor growth, angiogenesis, and pulmonary metastasis, in vivo. KSG-002 further decreased the infiltrated macrophage numbers in xenograft tumor cohorts. In Raw264.7 cells, KSG-002 but not KSG-001 inhibited cell proliferation and migration and reduced TNF-alpha (TNFα) production by inhibiting NF-κB pathway. Furthermore, a combinatorial treatment of KSG-002 with TNFα inhibited a proliferation and migration of both MDA-MB-231 and Raw264.7 cells. Taken together, we conclude that KSG-002 suppresses breast cancer growth and metastasis through targeting NF-κB-mediated TNFα production in macrophages.